Latin America: Where urbanization and poverty peak together with biodiversity? - Sanchez-Sarria, Camilo E.; Bonilla-Moheno, Martha; Vázquez, Luis-Bernardo; MacGregor-Fors, Ian (Springer, 2025)
Latin America is a region that houses many of the global biodiversity hotspots. Latin American countries are also well known for their social inequality and poverty. Simultaneously, most countries within the region concentrate their population within urban centers. Actually, among the five most populated global megacities, two are Latin American. In this chapter, we describe the region’s history of urbanization and socio-economy, examine the urban–biodiversity relationships that prevail in cities, and dissect the relationship that exists between the countries’ urbanization, their poverty levels, and their biodiversity (considering bird diversity as a proxy). For practical matters, we focused on major Latin American countries (>3 million people) for which official data are available. Our results show that Latin America is a biodiverse and socio-economically complex region, but it is also heterogeneous. Some countries showed to be tightly linked to one or two of the assessed variables, while others lied in intermediate values. For instance, some countries positively associated with urbanization but not with poverty or biodiversity (e.g., Chile, Uruguay), others related with high urbanization and poverty values (e.g., Puerto Rico, El Salvador), others with high poverty (e.g., Guatemala, Honduras), or high biodiversity (e.g., Peru, Brazil, Colombia, Ecuador, Bolivia). Thus, our results do not only highlight the peculiarities of each country but the heterogeneous reality of these relationships across the region.